2020
DOI: 10.1002/ps.6065
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Metarhizium anisopliae and Beauveria bassiana with insecticides and fungicides used in macadamia production in Australia

Abstract: Background Integrating fungal biocontrol agents into crop protection programs dominated by synthetic pesticides is an important first step towards developing an integrated pest management (IPM) program; however, their successful integration relies on an understanding of how their performance may be impacted by the remaining agrochemicals deployed for managing other pests and diseases. In this study we tested 10 formulated pesticides used in macadamia production at different concentrations to determine their ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 47 publications
0
10
0
2
Order By: Relevance
“…These strains have been lodged in the Queensland Plant Pathology Herbarium, Department of Agriculture and Fisheries, Brisbane, with accession numbers BRIP 70,272 (ECS1) and BRIP 70,267 (B27). Strain ECS1 was cultured on sterile Sabouraud dextrose agar supplemented with 1% (w/v) yeast extract (SDAY) 49 and strain B27 was cultured on sterile malt extract agar (MEA) media 49 . All fungal strains were incubated in the dark at 25 ± 1 °C for 15 days before harvesting the conidia for experimentation.…”
Section: Fungimentioning
confidence: 99%
“…These strains have been lodged in the Queensland Plant Pathology Herbarium, Department of Agriculture and Fisheries, Brisbane, with accession numbers BRIP 70,272 (ECS1) and BRIP 70,267 (B27). Strain ECS1 was cultured on sterile Sabouraud dextrose agar supplemented with 1% (w/v) yeast extract (SDAY) 49 and strain B27 was cultured on sterile malt extract agar (MEA) media 49 . All fungal strains were incubated in the dark at 25 ± 1 °C for 15 days before harvesting the conidia for experimentation.…”
Section: Fungimentioning
confidence: 99%
“…The formulation additives for these insecticides included toluene and xylene‐type aromatic solvents, which were toxic to the EPF. Our previous in vitro study examining the effects of beta‐cyfluthrin and methidathion in EC and non‐EC formulations also showed that beta‐cyfluthrin at 12.5 mg AI/L and methidathion at 250 mg AI/L without EC formulation additives were compatible with M. anisopliae strain QS155 and B. bassiana strain B50 but when EC formulations were tested at the same active ingredient concentrations they were toxic to both fungal species (Khun et al., 2021a).…”
Section: Discussionmentioning
confidence: 96%
“…Our previous in vitro study examining the effects of the insecticides acephate and indoxacarb at concentrations between 6.25% and 100% of their respective FFCs showed that these insecticides had no detrimental effect on the conidial germination, growth and sporulation of M. anisopliae strain QS155 or B. bassiana strain B50 (Khun et al., 2021a). In this study, both insecticides were mixed directly with M. anisopliae strain ECS1 and B. bassiana strain B27 in order to simulate a tank mixture for orchard spraying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, as interações, principalmente as negativas, devem ser consideradas nos programas de Manejo Integrado de Pragas (MIP), pois, quanto mais seletivo e compatível for o produto químico mais eficiente será a conservação do entomopatógeno (Silva et al, 2005). Este aspecto é mais importante em agroecossistemas onde o fungo entomopatogênico é um importante fator para a redução populacional de insetos pragas, sendo considerado um inimigo natural-chave (Khun et al, 2021).…”
Section: Introductionunclassified